Hidrometrocolpos. - Suárez Senespleda, Felipe; Urbizo Cañón, Miguel; Montes de Oca Rodríguez, Eloy; García Suárez, Manuel; Zamora Rodríguez, Héctor (Revista Cubana de Pediatría, 2023)
Se presetna el caso de una recién nacida con hidrometrocolpos congénito.